Revitalization Strategy of "Asta Tinggi" Tourist Destination Based on Cultural Identity and Creative Industry in Sumenep, Madura - Medhy Aginta Hidayat; Mutmainnah Mutmainnah (Jurnal Syntax Admiration, 2024)
This study examines the strategy for the revitalization of the Asta Tinggi religious tourism area by utilizing the cultural identity and creative industries in Madura, Indonesia. More specifically, the revitalization strategy considers the active-collaborative involvement of the stakeholders. This study used a qualitative approach, with a phenomenological method. The primary data were obtained through field observations and in-depth interviews. Secondary data were obtained through literature references, news media, scientific documentation, pictures, and photos. This study found that the best model for the revitalization strategy of the Asta Tinggi religious tourism area must involve the Sumenep Palace family, the Asta Tinggi management unit, the private sectors, local communities, and local governments. The role of the Sumenep Palace family and the management of Asta Tinggi is very important because they have the rights and authority to manage the Asta Tinggi. The revitalization of this religious tourism area should be pursued by prioritizing the cultural identity of Madurese and the potential of digital-based creative industries. With this revitalization strategy model, it is hoped that the Asta Tinggi can be developed as a leading religious tourism destination in Madura, Indonesia.